2009
DOI: 10.1590/s1414-32832009000500011
|View full text |Cite
|
Sign up to set email alerts
|

Humanização na atenção a nascimentos e partos: breve referencial teórico

Abstract: Apesar da ampliação da cobertura da atenção pré-natal e hospitalização do parto, houve estabilização no coeficiente de mortalidade materna em valores relativamente altos, atribuída aqui à qualidade inadequada da atenção. Um dos componentes do processo de assistência é a relação interpessoal, à qual tem sido associado o conceito de humanização. Identifica-se um forte movimento internacional que aborda a humanização da atenção a nascimentos e partos como uma resposta à mecanização na organização do trabalho prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
72

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 9 publications
0
17
0
72
Order By: Relevance
“…Although the Brazilian issue on access to prenatal care in basic care units is on the way to being solved 10 , this study reiterates the persistent problems of prenatal care quality 16,17 and revealed difficulties in obtaining specialized services characterized by inadequacy of reproductive risk management, difficult relationship with health professionals, besides absence of an organized assistance network to guarantee care provision, for example, through reference and counter-reference systems. Studies on healthcare provision to hypertensive pregnant women correlate the inadequacy of prenatal care mainly to professional fault, at the technical or human relations plan 9,16 .…”
Section: Comunicação Saúde Educaçãomentioning
confidence: 68%
“…Although the Brazilian issue on access to prenatal care in basic care units is on the way to being solved 10 , this study reiterates the persistent problems of prenatal care quality 16,17 and revealed difficulties in obtaining specialized services characterized by inadequacy of reproductive risk management, difficult relationship with health professionals, besides absence of an organized assistance network to guarantee care provision, for example, through reference and counter-reference systems. Studies on healthcare provision to hypertensive pregnant women correlate the inadequacy of prenatal care mainly to professional fault, at the technical or human relations plan 9,16 .…”
Section: Comunicação Saúde Educaçãomentioning
confidence: 68%
“…In this context, Rattner (19) states that the presence of a significant companion for the women is the best "technology" available for a successful delivery. The author emphasizes that women who had continuous emotional support during labor and childbirth were less likely to receive analgesia, to have cesarean section and who reported greater satisfaction with the experience.…”
Section: Discussionmentioning
confidence: 99%
“…Trata-se, portanto, de uma violência (física e simbólica) que muitas vezes também ocorre sob o disfarce de normalidade, podendo ser atribuída à grande parte das mulheres que adentram às instituições de saúde para dar à luz e acabam vivenciando procedimentos de rotina, que, em realidade, não deveriam ser rotina (OMS, 1996;Rattner, Amorim, Katz, 2013;Davis-Floyd e outros, 2009;Odent, 2005aOdent, , 2005bBrasil, 2011).…”
Section: Blogs E a Humanização Do Partounclassified